2000
DOI: 10.2337/diabetes.49.3.392
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and functional characterization of muscarinic receptor subtypes in insulin-secreting cell lines and rat pancreatic islets.

Abstract: Expression of muscarinic receptors in rat islets, RINm5F cells, and INS-1 cells was established by reverse transcriptase-polymerase chain reaction (RT-PCR) a n d q u a n t i fied by RNase protection. Both methods indicated that m3 and m1 receptors were expressed approximately equally in the various cellular preparations and to a much greater extent than the m5 subtype. However, the cell lines, especially RINm5F cells, expressed less of a given receptor subtype than did islets. Immunohistochemistry indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
5
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 10 publications
6
65
5
1
Order By: Relevance
“…Similar findings were obtained with rat pancreatic islets (23,25). Whereas previous studies (24,25) reported the expression of additional muscarinic receptor subtypes (M 4 or M 5 ) in islet preparations or in ␤-cellderived cell lines, we did not detect M 2 , M 4 , or M 5 receptor mRNA in mouse pancreatic islets. Because the majority of the cells in rat or mouse islets represent ␤-cells, it is highly likely that both M 1 and M 3 receptors are expressed by the insulin-secreting ␤-cells.…”
Section: Discussioncontrasting
confidence: 33%
See 1 more Smart Citation
“…Similar findings were obtained with rat pancreatic islets (23,25). Whereas previous studies (24,25) reported the expression of additional muscarinic receptor subtypes (M 4 or M 5 ) in islet preparations or in ␤-cellderived cell lines, we did not detect M 2 , M 4 , or M 5 receptor mRNA in mouse pancreatic islets. Because the majority of the cells in rat or mouse islets represent ␤-cells, it is highly likely that both M 1 and M 3 receptors are expressed by the insulin-secreting ␤-cells.…”
Section: Discussioncontrasting
confidence: 33%
“…Molecular cloning studies have revealed the existence of five molecularly distinct muscarinic receptor subtypes (M 1 ϪM 5 ) (22). Receptor localization studies suggest that multiple muscarinic receptors (M 1 , M 3 , M 4 , and M 5 ) are expressed in pancreatic islets/␤-cells or ␤-cellϪderived tumor cell lines (23)(24)(25). However, the M 3 muscarinic receptor appears to be the predominant subtype expressed by pancreatic ␤-cells (4 -6,23-25).…”
mentioning
confidence: 99%
“…To explore the mechanism that links enhanced β cell G q signaling to increased IRS2 expression, we used a rat insulinoma cell line (INS1-M3) as a model system (14). This cell line expresses moderate levels of the M 3 muscarinic receptor subtype, a prototypic G q -coupled receptor (15).…”
Section: Introductionmentioning
confidence: 99%
“…␤-cells with ACh or the cholinergic agonist carbachol before a glucose challenge resulted in a higher potentiation of GSIS compared with unprimed ␤-cells (21,42). Furthermore, treatment of HC islets with 4-DAMP in the presence of ACh resulted in significant reductions in cholinergic-induced insulin secretion, suggesting that ACh-induced potentiation of GSIS is mediated through activation of M3R as seen in a study showing that potentiation of GSIS by the cholinergic agonist oxotremorine M is inhibited by 4-DAMP (8).…”
Section: Discussionmentioning
confidence: 99%